Radiobiological model applicability in radiotherapy: single and fractionated irradiation - Ariffin, Nurul Akmal (Universiti Sains Malaysia, 2016)
The effect of fractionation had been experimentally proven to increase the surviving fraction of the cells instead of single irradiation. Cell survival described by radiobiological models could be used to predict the radiosensitivity and sublethal damage repair of cells to radiation. In this study, the linear quadratic (LQ) and multitarget (MT) cell survival curve models were used to describe the cell survival with single and fractionated irradiation. The applicability of both models in radiotherapy was investigated. HeLa cells were irradiated using 6 MV photon beam with 10><10 cm2 field size, 100 cm SSD at different doses. Standard clonogenic assay was performed to determine the cell survival. The experimental data were fitted to the LQ and MT model using OriginPro 9.2 software. Radiobiological parameters were evaluated from the fitting curves generated from these models. Fitting curve of the LQ and MT models for cell survival with single irradiation were found to be close to the experimental data. The survival curves fitted with LQ and MT model for single irradiation displayed steep initial slope and small shoulder. The sublethal damage repair was better for fractionated irradiation with wider shoulder. The parameters of LQ model showed a larger a and a/p ratio whereas for MT model showed a smaller n, Do and Dq. The parameterisation of LQ and MT model showed that single irradiation is more effective in reducing the number of cell survive. MT model seem to be more accurate in describing the radiosensitivity of the cells especially at high dose for both single and fractionated irradiations because the experimental data plotted fitted closely to the curve. The most commonly used model, LQ seem to provide unsatisfactory fitting at high dose.